Pengaruh Pemanfaatan Media Sosial dan Sistem Informasi Akuntansi Terhadap Minat Berwirausaha Mahasiswa Generasi Z - Oliviana Oliviana; Yety Sumayyah; Al Iqrom Septari; Yulia Novita (CV Muara Edukasi, 2025)
The development of digital technology has changed the learning patterns, consumption behavior, and career orientation of Generation Z, including in the context of entrepreneurship. Social media now functions not only as a means of communication, but also as an instrument for learning, business branding, digital marketing, and the formation of a business identity. On the other hand, the use of accounting technology such as Accounting Information Systems (AIS) is increasingly crucial to support transaction recording, financial management, and business decision-making. This study uses a systematic literature review approach based on empirical articles from 2019–2025 to analyze the influence of social media and AIS utilization on the entrepreneurial interest of Generation Z students. The synthesis results show that social media has a positive effect by providing access to business information, inspiration, and ease of marketing. Meanwhile, AIS strengthens students' confidence in running a business through accurate financial recording, cash flow management, and financial reports that support strategic decisions. These two variables have been shown to influence entrepreneurial interest more optimally when supported by digital literacy, entrepreneurial knowledge, and self-efficacy. This study emphasizes the importance of integrating digital technology-based entrepreneurship education and accounting to prepare competent young entrepreneurs